Non-linear relationship between social jetlag and depressive symptoms among Chinese college students - Jing Luo; Jinyou Yang; Tianjiao Dai; Jing Zhao; Shasha Wu; Linlu Zhou; Hong Ge; Beilei Yan; Yunyun Liu; Yuling Zhang; Jiru Wang; Wenqin Yin; et al. (Scientific Reports)
Abstract This study aims to elucidate the relationship between social jetlag and depressive symptoms in college students, with a focus on identifying specific cut points that significantly heighten the risk of depression. A cross-sectional study was conducted among 2,006 students from Jiangsu College of Nursing between October and November 2024. Social jetlag was calculated based on the difference between the midpoints of sleep on workdays and weekends. Depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). Multivariate logistic regression was applied to examine the relationship between social jetlag and depressive symptoms, adjusting for potential confounders. The prevalence of depressive symptoms (PHQ-9 ≥ 10) among participants was 10.1%. A non-linear relationship was observed between social jetlag and depressive symptoms, with the risk of depression increasing significantly beyond a threshold of 1.2 h of social jetlag. Specifically, individuals with social jetlag ≥ 1.2 h had 72% higher odds of depressive symptoms compared to those with lower levels (OR = 1.72, 95% CI: 1.24–2.38). Subgroup analyses revealed that this association was consistent across both grade and gender. Sensitivity analyses further affirmed the robustness of these findings. This study suggests a non-linear association between social jetlag and depressive symptoms in college students, with a marked increase in depression risk for those with social jetlag ≥ 1.2 h. Longitudinal studies are needed to clarify the causal pathways and identify modifiable factors for targeted interventions.